Pendidikan Agama sebagai prevensi pernikahan dini: analisis terhadap pemahaman dan praktik agama dalam mengatasi fenomena pernikahan dini di Pekanbaru - Mauludi, Syahrul (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
Erly-age marriage remains a severe issue in Indonesia, including in Pekanbaru. This phenomenon seriously impacts individuals and society, including poor reproductive health, low education and skills, social and emotional problems, financial issues, and family problems. This study analyzed the religious understanding and practices in the Pekanbaru community related to early-age marriage through a descriptive qualitative approach. The results indicated that adolescents' common religious knowledge and lack of religious education were the main factors contributing to the early-age marriage. This research advises enhancing religious education in schools and communities and teaching concepts such as gender equality, children's rights, and social responsibility to improve public awareness and prevent early-age marriage in Pekanbaru.